KDM2B recruitment of the Polycomb group complex, PRC1.1, requires cooperation between PCGF1 and BCORL1 - Wong, Sarah J. (Structure, 2016)
KDM2B recruits H2A-ubiquitinating activity of a non-canonical Polycomb Repression Complex 1 (PRC1.1) to CpG islands, facilitating gene repression. We investigated the molecular basis of recruitment using in vitro assembly assays to identify minimal components, subcomplexes and domains required for recruitment. A minimal four-component PRC1.1 complex can be assembled by combining two separately isolated subcomplexes: the DNA binding KDM2B/SKP1 heterodimer and the heterodimer of BCORL1 and the core PRC1.1 component PCGF1. The crystal structure of the KDM2B/SKP1/BCORL1/PCGF1 complex illustrates the crucial role played by the PCGF1/BCORL1 heterodimer. The BCORL1 PUFD domain positions residues preceding the RAWUL domain of PCGF1 to create an extended interface for interaction with KDM2B, which is unique to the PCGF1-containing PRC1.1 complex. The structure also suggests how KDM2B might simultaneously function in PRC1.1 and an SCF ubiquitin ligase complex and the possible molecular consequences of BCOR PUFD internal tandem duplications found in pediatric kidney and brain tumors.